Cadmium Chloride (CdCl2)-Induced Apoptosis in Liver of Mice - Gathwan, Khalid Hamdan (Journal of the Faculty of Medicine Baghdad, 2006)
Background: Cadmium (Cd) is an industrial and environmental pollutant that affect adversely a number of organs in humans and other mammals. Objectives: To study the effect of cadmium on liver of mice. Material and Methods: Male Balb/c mice weighing 30-32 gm, 60 days old, were treated intraperitoneally (ip) with (1-10mg/kg body wt. /CdCl2). The body weight, liver weight, histological examination of liver, SEM, metal analysis along with DNA ladder for apoptosis. Results: Cadmium induced both a time, and dose dependent increase in apoptotic, severity of necrosis. Liver weight, body weight decreased with increase of dose, while metal content was increased by increase of dose. Conclusion: It has been concluded that cadmium caused necrotic effect on liver and apoptotic as well as decreased body weight and liver weight.